PENGARUH INTELLECTUAL CAPITAL, PROFITABILITAS DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN - Retno Indar Dwi Dhevanti; Budiyono Budiyono; Suprihati Suprihati (ITB AAS INDONESIA, 2022)
This study aims to examine and determine whether there is an influence of intellectual capital, profitability and debt policy on firm value. This type of research uses quantitative research methods and the data used in this study are secondary data. The population of this research is Kompas 100 companies listed on the IDX in 2019-2021. The sampling technique used purposive sampling method so that 72 samples were found. The results showed that the variables of intellectual capital, profitability and debt policy had a significant positive effect on firm value. Coefficient test determination shows the value of Adjusted R Square of 0.876 indicating that the influence of intellectual capital, profitability and debt policy on firm value is 87.6%.